Relationship between intraindividual auditory and visual attention in children with ADHD. (January 2021) - Lin, Hung-Yu; Chang, Wen-Dien; Hsieh, Hsieh-Chun; Yu, Wan-Hui; Lee, Posen
Highlights: Children with ADHD may have attention deficiency on one modality but not necessarily on the other. Typically developing children display more consistent attentional performance than children with ADHD. The attentional mechanism responded for concentration was modality-specific. Reaction time variability is the most important diagnostic indicator of ADHD. Reaction time is not a reliable diagnostic indicator of ADHD. Abstract: Background and aim: Most previous attention-deficit/hyperactivity disorder (ADHD) studies have used only a single sensory modality (usually vision) to investigate attentional problems, although patients with ADHD might display deficits of auditory attention similar to their visual attention. This study explored intraindividual auditory and visual attention in children with and without ADHD to examine the relationship between these two dimensions of attention. Methods: Attentional performances of 140 children (70 children with ADHD and 70 typically developing peers) were measured through the Test of Variables of Attention (TOVA) in the present study. Results: For both groups, most attentional indices showed significant differences between the two modalities ( d ranging from 0.32 to 0.72). The correlation coefficients of most of the attentional variables in children with ADHD were lower than their typically developing peers. All attentional indices of children with ADHD (ranging from 12.8%–55.7%) were much higher than those of their typically developing peers (ranging from 1.4%–8.6%). Conclusion: These results not only indicate that typically developing children display more consistent attentional performance, but also support the view that children with ADHD may show attention deficiency in one modality but not necessarily in the other.